2002
DOI: 10.33584/jnzg.2002.64.2470
|View full text |Cite
|
Sign up to set email alerts
|

Once-a-day milking: possible and profitable?

Abstract: Once-a-day (OAD) milking offers a major opportunity to improve labour output on New Zealand farms. However few full lactation studies have been undertaken to investigate the effect of this strategy on the productivity of the farm system. A trial was established in 2000 to measure the effect of milking frequency and breed in farm systems where stocking rate was adjusted to equalise per hectare feed demand in different herds. There were four treatments: two herds of 35 Friesian and 42 Jersey cows, at 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
3
4
0
Order By: Relevance
“…Mean values of daily yields per cow of milk, fat and protein obtained from herd tests were slightly higher than yields calculated from milk vat records. Moreover, mean yields reported here were about 46%, 50% and 51% higher than the yields of milk, fat and protein, respectively reported in other comparable studies involving once a day milking but higher stocking rates (>3 cows/ha) [25][26][27]. Despite the differences in yields, mean live weights used here were within the ranges of live weights reported in the studies mentioned before (from 375 to 511 kg).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Mean values of daily yields per cow of milk, fat and protein obtained from herd tests were slightly higher than yields calculated from milk vat records. Moreover, mean yields reported here were about 46%, 50% and 51% higher than the yields of milk, fat and protein, respectively reported in other comparable studies involving once a day milking but higher stocking rates (>3 cows/ha) [25][26][27]. Despite the differences in yields, mean live weights used here were within the ranges of live weights reported in the studies mentioned before (from 375 to 511 kg).…”
Section: Discussionsupporting
confidence: 61%
“…Likewise, herbage mass measures at pre-grazing were within normal ranges observed for ryegrass dominant herbage swards (from 2200 to 3700 kg DM/ha) [1,29] while herbage mass measures obtained at post-grazing were slightly higher than the most frequent measures observed by McCarthy et al [30], which ranged from 1480 to 1760 kg DM/ha. Higher than normal post-grazing residuals might help explain the higher yields measured in this study compared to those reported in other comparable studies [25][26][27].…”
Section: Discussionsupporting
confidence: 51%
“…The major disadvantage of once-daily milking is reduced milk production. Losses reported in previous experiments ranged from 7 to 38% for part-lactation periods of once-daily milking (Davis et al, 1998) and losses from full lactations ranged from 22 to 35% in New Zealand studies (Holmes et al, 1992;Tong et al, 2002). Wide variation in production losses of individual cows (compared with those of identical twins milked twice daily or with their previous twice-daily production) has been observed, ranging from 0 to 47% in part-lactation studies (Claesson et al, 1959;Carruthers et al, 1989), and from 5 to 85% in full-lactation studies (Claesson et al, 1959;Holmes et al, 1992).…”
Section: Introductionmentioning
confidence: 92%
“…In this study while milk fat yield and percentage was increased in OAD cows compared to TAD cows neither was significantly higher, protein percentage was significantly higher, as similarly seen to previous research (Stelwagen et al, ). Variation in SCC has been previously observed, where OAD cows had higher SCC than cows milked TAD (Lacy‐Hulbert, ; Rocha et al, ; Tong, Clark, & Cooper, ). While there was no significant difference in the average LW of the two milking cohorts, the change in LW was, with OAD increasing and TAD decreasing.…”
Section: Discussionmentioning
confidence: 77%